2014
DOI: 10.4236/sm.2014.42017
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime Prevalence of Emotional/Psychological Abuse among Qualified Female Healthcare Providers

Abstract: The purpose of this study was to determine the lifetime prevalence of emotional/psychological abuse among married female healthcare providers in tertiary care hospitals in Karachi, Pakistan. A descriptive cross-sectional study was conducted in a sample of 350 married female nurses and doctors, recruited from three tertiary healthcare hospitals (one public and two private). This study used the self administered modified truncated WHO multi-country questionnaire. Descriptive and univariate analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
1
6
0
Order By: Relevance
“…None of these studies were Australian. The lifetime prevalence rate ranged between 3.7% (doctors in the United States) [ 17 ] and 97.7% (doctors and nurses in Pakistan) [ 18 ]. A large study conducted in a country with a comparable population prevalence rate to Australia is that by Bracken et al (2010) in the United States [ 12 ], who surveyed 1981 nurses and found that the lifetime physical or sexual IPV prevalence rate was 25%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of these studies were Australian. The lifetime prevalence rate ranged between 3.7% (doctors in the United States) [ 17 ] and 97.7% (doctors and nurses in Pakistan) [ 18 ]. A large study conducted in a country with a comparable population prevalence rate to Australia is that by Bracken et al (2010) in the United States [ 12 ], who surveyed 1981 nurses and found that the lifetime physical or sexual IPV prevalence rate was 25%.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of the few studies on this issue include: a lack of rigor in the assessment of IPV [ 12 , 14 , 16 , 17 , 20 , 22 ], low or unpublished response rates [ 20 , 23 , 26 ], small sample sizes [ 21 , 23 , 24 ], or publication ten or more years ago [ 15 17 , 24 , 25 ]. Another feature of these studies is their diversity: six of the studies were conducted in countries where a language other than English is the official language [ 15 , 16 , 18 , 19 , 21 , 23 ], and in some countries prevalence studies were hard to generalise to the Australian context since the population prevalence was substantially higher than reported in the Australian community [ 18 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The abusive behavior started delicately, propelled and pushed way the survivor from the family, as time passed it heat up and appear harmful. According to the concluding remarks of Khan et al (2014), it is existed in every culture, religion and society but third world country suffering more than developed countries. It is observed that controlling behavior of husband and mother-inlaw is also very important factor.…”
Section: Gender Differences and Domestic Violencementioning
confidence: 99%
“…Across all the previous studies, the prevalence of DFV against nurses has most commonly reflected broader community DFV prevalence in the places where the research was conducted [ 16 , 17 , 19 , 22 , 25 , 27 , 30 ]. However, where a difference between DFV against nurse participants and the general community was detected, it was more likely that nurses reported a higher prevalence of DFV [ 8 , 9 , 18 , 23 , 24 ] compared to the general community. Only two studies have investigated the perpetration of violence against a partner by nurses [ 21 , 24 ], and only one separated their results by gender, finding that 16.0% of 45 men and 21.4% of 294 women reported that they had ever perpetrated physical IPV [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were not without limitations and these included: small sample sizes ( n < 100) [ 16 , 26 , 27 , 31 , 32 ]; long recall period (> 12-months) [ 16 , 18 23 , 26 , 28 – 32 ]; lack of use of a validated IPV measure [ 17 , 21 , 22 , 31 ]; low (< 10%) or unpublished response rate [ 8 , 18 , 21 , 25 , 27 , 28 , 32 ], and results not separated by gender [ 21 ]. Only one study has been conducted in Australia and utilised a small sample of 471 women health professionals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%